Obstructed pedunculated jejunal gastrointestinal Stromal tumor disguise as pelvic mass - a case report - Izhar, NA; Shamil, S; Salmi, Irfan; Elagili, Faisal; Md Nor, Azmi (2023)
INTRODUCTION: Obstructed pedunculated jejunal gastrointestinal stromal tumours (GISTs) are very rare and can be misdiagnosed as gynaecological masses. OBJECTIVE: We are describing a rare case of small bowel obstruction caused by a jejunal GIST misdiagnosed as an ovarian mass. CASE REPORT A 70-year-old lady presented with abdominal pain, vomiting, and no bowel movement for three days prior. Clinical abdominal examination reveals a palpable mass at the level of the umbilicus, which was unable to feel the lower border of it. Contrasted CT Abdomen revealed a solid cystic mass in the pelvis, suspected to be ovarian in origin and associated with small bowel dilatation. The patient was subjected to exploratory laparotomy, which revealed a 12x13cm pedunculated mass from the jejunum 115cm from the duodenojejunal junction. The lesion was twisted and caused small bowel dilatation. The lesion was resected at the base of the peduncle using a linear stapler. Pathology was confirmed to be a high-risk GIST with a clear margin. The patient's postoperative course was uneventful, and she was discharged on the third postoperative day. The patient is currently receiving adjuvant imatinib therapy. CONCLUSION: Obstructed pedunculated jejunal GIST is a very rare disease and challenging to diagnose. It should be considered in patients with small bowel obstruction and pelvic mass. Resection at the peduncle base is safe and provides a clear oncological resection margin.